2022
DOI: 10.3389/fpls.2022.947547
|View full text |Cite
|
Sign up to set email alerts
|

Co-inoculation of biochar and arbuscular mycorrhizae for growth promotion and nutrient fortification in soybean under drought conditions

Abstract: Drought is significant abiotic stress that affects the development and yield of many crops. The present study is to investigate the effect of arbuscular mycorrhizal fungi (AMF) and biochar on root morphological traits, growth, and physiological traits in soybean under water stress. Impact of AMF and biochar on development and root morphological traits in soybean and AMF spores number and the soil enzymes’ activities were studied under drought conditions. After 40 days, plant growth parameters were measured. Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 79 publications
1
12
0
Order By: Relevance
“…The plant's survival during a drought is guaranteed by PGPR through a variety of mechanisms, including osmotic adjustments, increased antioxidant activity, phytohormone production, etc., and these mechanisms also promote the plant's growth. Additionally, new developments in omics technologies have improved our understanding of PGPR, which makes it easier to investigate the genes involved in colonizing plant tissue (Baba et al, 2021; Jabborova et al, 2021, 2022; Kapadia et al, 2021; Kapadia, Kachhdia, et al, 2022; Kapadia, Patel, et al, 2022; Khan et al, 2021; Khumairah et al, 2022).…”
Section: Role Of Pgpr In Combating the Abiotic Stressmentioning
confidence: 99%
“…The plant's survival during a drought is guaranteed by PGPR through a variety of mechanisms, including osmotic adjustments, increased antioxidant activity, phytohormone production, etc., and these mechanisms also promote the plant's growth. Additionally, new developments in omics technologies have improved our understanding of PGPR, which makes it easier to investigate the genes involved in colonizing plant tissue (Baba et al, 2021; Jabborova et al, 2021, 2022; Kapadia et al, 2021; Kapadia, Kachhdia, et al, 2022; Kapadia, Patel, et al, 2022; Khan et al, 2021; Khumairah et al, 2022).…”
Section: Role Of Pgpr In Combating the Abiotic Stressmentioning
confidence: 99%
“…Furthermore, according to Jabborova et al [ 4 ], adding biochar significantly increases the chlorophyll, nitrogen (N), and carbon (C) content of soybean plants in conditions resembling drought. Numerous studies [ 1 , 77 ] have reported that biochar can enhance the activity of protective enzymes and antioxidants in plants, which can mitigate the negative effects of drought stress on photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is essential to acknowledge that the harsh climate characteristic of arid and semi-arid regions stands as the primary factor limiting grain productivity. Indeed, various crops face substantial abiotic stress, notably drought stress (DS), which adversely affects their growth and yield [ 4 ]. During drought conditions, the soil's capacity to retain water diminishes, leading to osmotic stress that restricts the flow of water and nutrients to plants.…”
Section: Introductionmentioning
confidence: 99%
“…Also, in a study ( Yedidia et al, 2001 ), T203 isolates of T. harzianum increased the cucumber shoot length by 45% compared to the control. Possible mechanisms of Trichoderma -induced increased shoot length can be through promoting the efficiency of nutrient transport from soil to roots through pathways similar to mycorrhizal fungi ( Jabborova et al, 2022 ; Saboor et al, 2021 ; Najafi et al, 2021 ; Bastami et al., 2021 ). Plant peroxidases are significant in plant activities such as interfering with lignin biosynthesis, auxin metabolism, scavenging oxygen free radicals, providing resistance to oxidative stress, wound healing, etc.…”
Section: Discussionmentioning
confidence: 99%